Incidencia del nepotismo en los derechos de las persona de acuerdo al artículo 6 de la ley de servicio público del Ecuador - Punina Cajas, Maria Paula (2016)
This research was conducted because the rate of "IMPACT nepotism in public entities" of the country is high and one reason is the weakness of the laws, but also the lack of awareness towards the servants of the state to through training on how it affects citizens dreams consistently manage to choose a public office, also to the national treasury as any process of merit; Therefore in this research a critical study will be made to Article 6 of the Law on Public Service and for this reason it has taken into account the opinion of lawyers, professionals in the law and even to persons not related to the right to give us their views on how the incidence of nepotism in the public sector there results of this research are alarming, because there are officials and employees who commit these events to our law. For this reason, this proposal has focused on reforming a changed urgent as nepotism "hiring relatives is prohibited until the fourth degree of consanguinity and second degree, to positions of presidents or directors of a public institution that is indirectly managed by other public institution.